Analysis of Factors Influencing Hypertension in the Gedong Tataan Community Health Center Work Area - Muthia Permata, Amara; -, Adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Hypertension remains a major health problem in the Gedong Tataan Community Health Center. The highest incidence of hypertension was found in the Gedong Tataan Community Health Center out of 15 community health centers in Pesawaran Regency. To address this issue, it is necessary to study the risk factors for hypertension. Hypertension can be caused by several risk factors, such as stress, obesity, physical activity, exposure to cigarettes, and family history. The purpose of this study was to analyze the factors influencing the incidence of hypertension in the Gedong Tataan Community Health Center work area, Gedong Tataan District, Pesawaran Regency, in 2024. This quantitative study used a cross-sectional design. Purposive sampling was used, and 207 respondents met the inclusion criteria. Data analysis used the chi-square test and multivariate analysis using multiple logistic regression. The majority of respondents (115 respondents) had hypertension. 139 people (67.1%) experienced stress, 109 people (52.7%) were not obese, 184 people (88.9%) had moderate and heavy physical activity, 114 people (55.1%) had cigarette exposure, and 120 people (58.0%) had a family history. There was a significant relationship between stress (p-value = 0.002), obesity (p-value = 0.000), physical activity (p-value = 0.036), cigarette exposure (p-value = 0.000), family history (p-value = 0.000) with the incidence of hypertension. The results of the multivariate analysis of obesity were the dominant factor that could influence the incidence of hypertension in the Working Area of ​​the Gedong Tataan Health Center, Gedung Tataan District, Pesawaran Regency in 2024 (OR = 15.67). Conclusion: Stress, obesity, physical activity, exposure to cigarettes, and family history are risk factors associated with hypertension in the Gedong Tataan Community Health Center Work Area, Gedong Tataan District, Pesawaran Regency in 2024.